The Influence of Employee Engagement on Organizational Citizenship Behavior in Central Kalimantan Banking Industry - Anike Retawati; Muhammad Ruzaini Abdi; ⁠Arif Rahman Hakim (Sean Institute, 2025)
This research aims to analyze the influence of employee engagement on organizational citizenship behavior (OCB) in the banking industry of Central Kalimantan. The phenomenon of low voluntary employee behavior presents a challenge in enhancing service-oriented organizational performance. This research employs a quantitative approach using survey methodology with 120 bank employees in Palangka Raya, Sampit, and Pangkalan Bun. The employee engagement variable was measured through three dimensions—vigor, dedication, and absorption—while OCB was measured through five dimensions—altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. Multiple linear regression analysis revealed that employee engagement exerts a positive and significant influence on OCB with an R² value of 0.468 and p < 0.05. Among the three dimensions, dedication demonstrated the most dominant effect, indicating that pride and emotional commitment to work serve as the primary driver of extra-role employee behavior. The research results affirm that work engagement not only increases productivity but also strengthens collaborative work culture and loyalty toward the organization. Practical implications of this research involve the necessity of managerial strategies focusing on engagement development through performance recognition, open communication, and leadership support. These findings provide theoretical contribution to the development of organizational behavior studies and practical relevance for enhancing competitiveness of regional banking in Indonesia.